2012
DOI: 10.1002/cncr.27822
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant therapy with weekly docetaxel and cisplatin, 5‐fluorouracil continuous infusion, and concurrent radiotherapy in patients with locally advanced esophageal cancer produced a high percentage of long‐lasting pathological complete response

Abstract: BACKGROUND: This phase 2 study was aimed at defining the pathological response rate of a neoadjuvant schedule including weekly docetaxel and cisplatin, continuous infusion (c.i.) of 5-fluorouracil (5-FU) and concomitant radiotherapy (RT) in untreated stage II-III adenocarcinoma and squamous cell carcinoma of mid-distal thoracic esophagus. METHODS: The schedule consisted of a first phase of chemotherapy alone and of a second phase of concurrent chemoradiation. Doses were as follows: docetaxel 35 mg/m 2 and cisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 44 publications
6
33
0
Order By: Relevance
“…However, the pCR rate after neoadjuvant CRT for the PF group (28.1%) was consistent with that of previous reports, which mainly comprised esophageal SCC (9.8-49%) [2,[4][5][6]. The 3-year OS rate for patients who received PF in our series (31.3%) was also within the wide range reported in the literature (27-61% at 3 years) [2][3][4][5][6][15][16][17][18][19][20]. Compared with PF, patients who received NP had a significantly higher pCR rate (47.4%) and superior survival.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the pCR rate after neoadjuvant CRT for the PF group (28.1%) was consistent with that of previous reports, which mainly comprised esophageal SCC (9.8-49%) [2,[4][5][6]. The 3-year OS rate for patients who received PF in our series (31.3%) was also within the wide range reported in the literature (27-61% at 3 years) [2][3][4][5][6][15][16][17][18][19][20]. Compared with PF, patients who received NP had a significantly higher pCR rate (47.4%) and superior survival.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, several retrospective studies have revealed that paclitaxel-based regimens did not result in superior pCR and survival compared to traditional fluorouracil-based chemotherapy [15][16][17]. The efficacy of three-drug, paclitaxel-containing regimens has been investigated as well [18][19][20]. Kelsey et al reported clinical results using PF versus paclitaxel/carboplatin/fluorouracil [19].…”
Section: Discussionmentioning
confidence: 97%
“…In malignancies such as rectal, esophageal and breast cancer, pCR has been associated with improved disease-free survival and OS (73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83). In PAC, a number of studies reported pathologic outcomes following neoadjuvant chemotherapy with or without fractionated radiotherapy or stereotactic body radiotherapy, and the pCR rate ranges between 2.4 and 32.0% (41,(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94).…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13]15,20,21 In general, the margin-free resection rate or 6-month progression-free survival is used as an effective surrogate marker of NACRT efficacy in PDA. The pathological response rate is also gaining recognition as an important surrogate.…”
Section: Discussionmentioning
confidence: 99%